Condições para o sucesso de empreendedores de startups de fase early-stage que buscam investimentos de capital-semente no Rio Grande do Sul: um método de orientação para empreendedores - Bastos, Bruno Pereira de (Universidade do Vale do Rio dos Sinos, 2020)
This research aims to propose a method of guidance for early-stage startup entrepreneurs seeking seed capital investments in Rio Grande do Sul (RS). Startups are initiatives by people looking for a business model that is replicable, scalable, and profitable in an environment of extreme uncertainty (BLANK 2014; RIES 2012). Startups are financed early-stage by seed capitalists. Investments of this size occur in smaller volumes, compared with other types, for startups and innovative companies. With reference to the mortality rates of Brazilian companies, 75% die in a period equal to or less than that of maturity and 50% in a period equal to or less than birth. Startups need funding to stay on hold. The problems of bankruptcy are mostly related to the aspects that could have been reversed if remedied in time. The theoretical benchmark contains topics such as Entrepreneurship, New Business, Investments and Tools and Models for startups. The research methodology, Design Science Research (DSR), contributed to the development of the proposed Method. To this end, interviews were applied with experts and investors of the seed type in the RS, which are: incubators and technology parks, accelerators, support and development institutions and angel investors. In the analysis and in the survey of data, the responses of these actors were taken into consideration, making possible the creation of the Method proposed in this research.
Keywords: Investimento-semente; Ecossistema de empreendedorismo; Inovação; Startup; Seed money; Entrepreneur ecosystem; Innovation; ACCNPQ::Ciências Sociais Aplicadas::Administração